Rekayasa Sistem Informasi Pembayaran Praktikum Dan Kerja Praktek Menggunakan Metode Waterfall - Hesti Wulan Sari; Wahju Tjahjo Saputro; Hamid Muhammad Jumasa (INTEK : Jurnal Informatika dan Teknologi Informasi, 2022)
The administrative section of Purworejo Muhammadiyah University Information Study Program in processing data payment works and practice work still uses a manual process that is using Microsoft Excel. Furthermore, management should keep payment slips as evidence that the student has already made the payments. As for the weakness of the payment slip that can be lost and after several months the writing on the deposit slip fades. After all, it was not yet effective. Thus, researchers do research and construct Information Systems Payment Services and Practical work on Information Technology Study Programs. This information system was created to make it easier for the governance part in managing the payment data both practical and practical. The method of data collection used in this research is observation, interview, and library study. The method used for system development is the waterfall method. In addition, payment information systems are built with PHP programming language, the framework Code of Igniter, and MySQL databases. Research indicates the waterfall method can be used to design a system of payment information, practical and practical. Systems can be used with a record of several improvements to the functional aspect. Development of implemented study and policy programs.